Trend Issues of Using AI Tools In Foreign Language Teaching Context: Bahasa English - Jelita, Seri; Elina Bayusri; Rike Meyla Eka Saputri; Nitia Oktavilady; Erwin Pohan (CV. Kalimasada Group Profesional, 2025)
Advances in artificial intelligence (AI) technology have brought about significant transformations in foreign language teaching (FLT). This article explores the opportunities, challenges, and implementation strategies of AI in foreign language learning, with a focus on personalization of learning, real-time feedback, and increased accessibility. AI enables adaptive learning approaches to suit individual needs, provides instant feedback that supports language skill development, and opens access to quality materials for students in different geographies. However, challenges such as traditional curriculum integration, algorithm bias, limited understanding of cultural context, and ethical issues of data privacy need to be overcome for optimal utilization of AI. Teacher involvement remains essential to provide guidance, motivation, and pedagogical adjustments in a holistic learning process.